Playing with reality : how games have shaped our world - Clancy, Kelly (Neuroscientist) (Riverhead Books, 2024)
"A wide-ranging intellectual history that reveals how important games have been to human progress, and what's at stake when we forget what games we're really playing. We play games to learn about the world, to understand our minds and the minds of others, and to make predictions about the future. Games are an essential aspect of humanity and a powerful tool for modeling reality. They're also a lot of fun. But games can be dangerous, especially when we mistake the model worlds of games for reality itself and let gamification co-opt human decision making. Playing with Reality explores the riveting history of games since the Enlightenment, weaving an unexpected path through military theory, political science, evolutionary biology, the development of computers and AI, cutting-edge neuroscience, and cognitive psychology. Neuroscientist and physicist Kelly Clancy shows how intertwined games have been with the arc of history. War games shaped the outcomes of real wars in nineteenth and twentieth century Europe. Game theory warped our understanding of human behavior and brought us to the brink of annihilation-yet still underlies basic assumptions in economics, politics, and technology design. We used games to teach computers how to learn for themselves, and now we are designing games that will determine the shape of society and future of democracy. In this revelatory new work, Clancy makes the bold argument that the human fascination with games is the key to understanding our nature and our actions"--